Tailors in the New World: the presence of Italian tailors in Brazil (1875-1906) - Conedera, Leonardo de Oliveira (2020)
This article aims to address the presence of Italian tailors in Brazil where several professionals have found opportunities to undertake their establishments in several Brazilian urban centers between the end of the 19th century and the beginning of the 20th. The source selected to carry out the research proposal exposed was the almanac Il Brasile and gli Italiani organized and published by the newspaper Fanfulla in 1906 in São Paulo. Therefore, from the almanac, it is intended to present and analyze the route of peninsular tailors who found a suitable space to exercise their craft in the Brazilian urban context during the late 19th and early 20th centuries.